Tingkat Pemahaman dan Minat Pengurus Dewan Kemakmuran Masjid Terhadap Financial Technology (Fintech) Syariah - Jefriyanto Jefriyanto; Didik Riyanto (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to examine the level of understanding and interest in the management of the Mosque Prosperity Council towards sharia fintech. This type of research built by the author is a quantitative descriptive study by conducting surveys. The population in this study is the Mosque Prosperity Council in Jakarta and its surroundings. The sample are the administrators of the Mosque Prosperity Council. The sampling technique used was random sampling, the sample used was 42 respondents. The results showed that the respondents had a good understanding and a high enough interest in fintech. However, for sharia fintech, respondents have less understanding and knowledge, even though they have a high enough interest for using sharia fintech in the mosque environment.